Comic book as an educational strategy to communicate fish bombing to schoolchildren - Lim, Voon-Ching; Richter, Isabell; Fadzil, Kamal Solhaimi; Goh, Hong Ching (Routledge, 2023)
Fish bombing impacts the marine ecosystem and local communities adversely, but is still being practiced in Sabah, Malaysia. To encourage more sustainable fishing practices, a creative educational strategy using a comic book was developed and evaluated in a marine protected area in Sabah. Questionnaire surveys and focus group discussions with 120 schoolchildren revealed that the comic book facilitated the improvement and retention of knowledge over time, knowledge sharing with family members, and growing intention to communicate the downsides of fish bombing to their community. This demonstrates the capability of comic books to convey sensitive environmental messages to coastal communities.